Perancangan Ilustrasi Cover Buku Untuk Menjadi Media Pengenalan Lingkungan Sosial Kepada Anak-Anak - Domenique Issabell Nhatassa Symonsz; Aninditya Daniar (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2023)
Designing illustrations in developing environmental socialization in developing children's awareness of social environmental problems. Illustrations are not just pictures but are also an effective communication tool. Illustrations are able to convey messages about protecting the environment in a way that is attractive to children. With a visual approach through illustrations, it can attract children's attention, enrich their learning experience, and trigger interest and participation in maintaining environmental curiosity. Apart from that, the role of illustration has been proven to be able to influence children's emotions regarding environmental problems, arouse their curiosity about new things, and deepen their understanding of the surrounding environment. Research methods that use an R&D approach focus on developing and evaluating illustration products to introduce children to the social environment, both in the school environment and in the family environment. The research results show that illustrations are very useful for children's socialization to make an important contribution in strengthening social interactions, triggering creativity, and deepening social relationships between children and their families or those around them.